Moving the andragogy of teacher educators forward: the potential and challenges of Problem-Based Learning in teacher education - Russell Grigg; Helen Lewis (Halla Newcastle Education and Research Center, 2018)
Objectives To explore the benefits of Problem-Based Learning (PBL) for pre-service trainee teachers, as a preparation for teaching in the primary school. Methodology A case study at one centre of teacher education in Wales is reported, using a pragmatic, mixed methods approach. The research tools used included semi-structured interviews, questionnaires, and analysis of videorecorded group meetings and module marks. Results Two hundred and eighty students (160 postgraduate and 120 undergraduate) responded to the questionnaire. Almost all report PBL to be highly motivating, engaging and relevant to teacher training. PBL modules had higher average marks for both postgraduate and undergraduate students than non-PBL modules. Interviews and video analysis with a focused group of fourteen students reveal perceived learning gains in applying theoretical knowledge to real-life problems, understanding multiple viewpoints and challenging assumptions. The greatest perceived challenges were self-directed research and time management. Conclusions Current discourse around the quality of initial teacher education in the UK focuses on institutional structures, location of training and leadership. We argue that PBL, and the quality of andragogy generally among teacher educators, should feature more strongly in these discussions.